Respuesta :

=> y = (2x + 1) / (x - 4) 
=> xy - 4y = 2x + 1 
=> xy - 2x = 4y + 1 
=> x(y - 2) = 4y + 1 
=> x = (4y + 1) / (y - 2) 
=> f-1(x) = (4x + 1) / (x - 2) 
subtitute x = 3 
=> f-1(3) = 13

As per the inverse of a function, the value of [tex]f^{-1}(3)[/tex] is 13.

What is the inverse of a function?

"An inverse function is defined as a function, which can reverse into another function."

The given function is

[tex]f(x) = \frac{2x+1}{x-4}[/tex]

⇒ [tex]y = f(x) = \frac{2x+1}{x-4}[/tex]

⇒ [tex]xy - 4y = 2x + 1[/tex]

⇒ [tex]xy - 2x = 4y + 1[/tex]

⇒ [tex]x(y - 2)= 4y + 1[/tex]

⇒ [tex]x = \frac{4y+1}{y-2}[/tex]

⇒ [tex]f^{-1}(x) = \frac{4y+1}{y-2}[/tex]

Now, [tex]f^{-1}(3) = \frac{4(3)+1}{3-2} = (12+1) = 13[/tex]

Learn more about inverse of a function here: https://brainly.com/question/2541698

#SPJ2

ACCESS MORE